2021
DOI: 10.1177/17446295211016180
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sexual developmental characteristics of adolescents with intellectual disabilities

Abstract: This cross-sectional study was carried out in order to determine the opinions of mothers on sexual development in children with intellectual disabilities. The sampling of this study included mothers of children aged 10–19 years with moderate and severe intellectual disabilities. Of the mothers, 45.7% stated that they felt incapable of providing sexual education to their adolescent children with disabilities and 97.6% stated that they had received no information on this subject themselves. Based on the mothers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In seven studies, [5,6,12,[16][17][18][19], only regular swimming was involved. In five studies, swimming formed a part of an aquatic intervention program [20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In seven studies, [5,6,12,[16][17][18][19], only regular swimming was involved. In five studies, swimming formed a part of an aquatic intervention program [20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The authors of [6,12] found that swimming for 30-90 min, 3 days per week, for 8-33 weeks, resulted in reduced body mass. However, other researchers [18,19] found that swimming for 60 min, 3 days per week, for 10-16 weeks did not affect body mass [18,19]. Similarly, some studies found that swimming for 50-90 min, 3 days per week, for 33-36 weeks resulted in decreased BMI [5,6,12], while other studies concluded that swimming for 45-60 min, 2-3 days per week, for 12-16 weeks, did not affect BMI values [16,17,19].…”
Section: When Considering Aquatic Interventions It Is Sometimes Diffi...mentioning
confidence: 94%
See 1 more Smart Citation
“…»to be continued« Use of a unified communication system, including pictorial aids and easyto-read texts, as an aid to patient-centred communication and the healthcare process. Top (2022) Sexual health education for adolescents with disabilities and their mothers leads to more effective sexual health management for this group of adolescents. Woodman, Simon, Hauari, & Gilbert (2020) Involving parents in their child's healthcare.…”
Section: Morris Muskat and Greenblatt (2018)mentioning
confidence: 99%
“…), which is particularly necessary in cases where parents have no one close by to support them or where there is social isolation (Taylor, Kong, Foster, Badawi & Novak, 2022), as well as when topics are not part of the routine (e.g. sex education for adolescents with disabilities) (Top, 2022). Collaboration during the healthcare process is important both between providers and children/adolescents and their parents (Arcuri et al, 2015; Woodman, Simon, Hauari, & Gilbert, 2020), involving professionals from different disciplines has an impact on treatment success (Morris, Muskat, & Greenblatt, 2018).…”
mentioning
confidence: 99%